Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1986
DOI: 10.1007/bf02013983
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of ciprofloxacin in healthy volunteers after oral and intravenous administration

Abstract: The pharmacokinetics of ciprofloxacin was studied in three groups of healthy volunteers comprising a total of 16 males and 16 females (age 21-35 years; body weight 52-80 kg). Single oral doses of 50, 100, 250, 500 and 750 mg were given to fasting subjects. The 250 mg dose was repeated after a breakfast. Intravenous doses of 50, 100 and 200 mg were given by short infusion in a randomized cross-over sequence. Concentrations of the drug in serum and urine were determined by high-performance liquid chromatography … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
46
3

Year Published

1987
1987
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(57 citation statements)
references
References 29 publications
7
46
3
Order By: Relevance
“…hours after intake (T ma J which is comparable to the data of Borner et al (1986), who investigated the pharmacokinetics in non-fasting healthy vo lunteers. Ciproftoxacin is rapidly excreted into the urine and high concentra tions were achieved even within 2 hours of drug intake.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…hours after intake (T ma J which is comparable to the data of Borner et al (1986), who investigated the pharmacokinetics in non-fasting healthy vo lunteers. Ciproftoxacin is rapidly excreted into the urine and high concentra tions were achieved even within 2 hours of drug intake.…”
Section: Discussionsupporting
confidence: 69%
“…Ciproftoxacin is rapidly excreted into the urine and high concentra tions were achieved even within 2 hours of drug intake. However, the half-life is considerably shorter in our patients (Table III) than in other studies where it was found to range between 3 and 5 hours (Wingender et al, 1984;Borner et al, 1986). High concentrations of ciproftoxacin were achieved in the urine and in most of the dosing interval by far exceeding the minimal concentrations necessary to inhibit growth of urinary tract pathogens (Wise et al, 1983;Fass, 1983).…”
Section: Discussioncontrasting
confidence: 57%
“…Ciprofloxacin, another parenteral quinolone, has biological half-lives of between 180 and 260 min (3,4,8,13,25), whereas biological half-lives of parenteral enoxacin (306 + 25 min [26]) and parenteral pefloxacin (630 + 90 min) were longer (10,26).…”
Section: Resultsmentioning
confidence: 99%
“…
In 10 volunteers, the pharmacokinetics of ofloxacin {HOE 280, DL 8280; (+)-9-fluoro-2,3-dihydro-3-methyl-10-(4-methyl-1-piperazinyl)-7-oxo-7H-pyrido-[1,2,3-deI [1,4] 1.4 liters/kg of body weight) suggested effective diffusion into the extravascular space. High total and renal clearances indicated primarily renal excretion with additional elimination pathways, such as tubular secretion and extrarenal elimination.
…”
mentioning
confidence: 99%
See 1 more Smart Citation